Prognostic value of red cell distribution width-to-platelet ratio in mortality of major burn in Sanglah Hospital Bali - Nyoman Siska Ananda; I Gusti Putu Hendra Sanjaya; Sianny Herawati; Agus Roy Rusly Hariantana Hamid; I Made Suka Adnyana; I Wayan Niryana (Intisari Sains Medis, 2022)
Introduction: The mortality rate in Sanglah Hospital due to major burns is quite high. The ratio of red cell distribution width (RDW) and platelet (PLT) (RPR) as a prognostic marker of mortality in major burns has never been studied in Indonesia. Calculations of RPR are easy, widely available and cost-efficient.Method: This study was retrospective observational case-control, with 60 patients with major burns consisting of 30 cases and 30 controls. Samples were taken from the Sanglah Hospital Medical Record Unit from April 2019 to April 2021. Cases were samples with mortality after day seven, while controls were samples that survived. RDW and PLT value on day seven are associated with the incidence of mortality.Results: The mean of RPR in the case group was higher than in the control group. RPR mean of the control group was 0.0559, and the case group was 0.0947 (p<0.001). The increase of RPR in the case group was 40.97%. Statistical analysis showed that high RPR was a significant mortality risk factor in patients with major burns (OR = 21.36; p < 0.001).Conclusion: High RPR is a prognostic marker of mortality in major burns at Sanglah Hospital.